041 Cognitive and neuropsychiatric effects of noradrenergic treatment in Alzheimer's disease: systematic review and meta-analysis. Issue 9 (12th August 2022) - David, Michael; Giovane, Martina Del; Liu, Kathy; Gostick, Benjamin; Oboh, Imafidon; Howard, Robert; Malhotra, Paresh
Abstract : Background: Dysfunction of the locus coeruleus-noradrenergic system occurs early in Alzheimer's disease. This results in a low-noradrenergic state in some patients, which contributes to cognitive and neuropsychi- atric symptoms. We aimed to assess the efficacy of noradrenergic drugs for improving these symptoms. Methods: The MEDLINE, Embase, and ClinicalTrials.gov databases were searched from 1980 to December 2021. We generated pooled estimates using random effects meta-analyses. Results: 19 randomised controlled trials, of which six studies were of 'good' quality, with seven 'fair' and six 'poor', included 1811 patients. Meta-analysis of 10 studies showed a small, significant positive effect of noradrenergic drugs on patients' global cognition, as measured using the MMSE or ADAS-Cog compared to placebo (SMD:0.14, 95%CI:0.03 to 0.25, p=0.01; I2=0%). No significant effect was seen on measures of attention (SMD:0.01, 95%CI:-0.17 to 0.19, p=0.91; I2=0). The apathy meta-analysis included eight trials and detected a large positive effect of noradrenergic drugs (SMD:0.45, 95%CI:0.16 to 0.73, p=0.002; I2=58%), although results were limited by potentially substantial heterogeneity. Discussion: Drug repurposing with established noradrenergic drugs, may offer safe and effective treatment in Alzheimer's disease, for both cognition and apathy. However, there are number of factors that should be considered before the design of much needed future clinical trials. Including, targeting the correct patient sub-groups and using the correct medications, at the optimal dose, possibly in combination with other treatments, in order to maximise therapeutic effect.